The Non-Coding RNAs Inducing Drug Resistance in Ovarian Cancer: A New Perspective for Understanding Drug Resistance - Li, Gaofeng; Gong, Jun; Cao, Shulong; Wu, Zhaoyang; Cheng, Dong; Zhu, Jia; Huang, Xuqun; Tang, Jingyi; Yuan, Yuning; Cai, Wenqi; Zhang, Haiyuan (Frontiers in Oncology, 2021)
Ovarian cancer, a common malignant tumor, is one of the primary causes of cancer-related deaths in women. Systemic chemotherapy with platinum-based compounds or taxanes is the first-line treatment for ovarian cancer. However, resistance to these chemotherapeutic drugs worsens the prognosis. The underlying mechanism of chemotherapeutic resistance in ovarian cancer remains unclear. Non-coding RNAs, including long non-coding RNAs, microRNAs, and circular RNAs, have been implicated in the development of drug resistance. Abnormally expressed non-coding RNAs can promote ovarian cancer resistance by inducing apoptosis inhibition, protective autophagy, abnormal tumor cell proliferation, epithelial-mesenchymal transition, abnormal glycolysis, drug efflux, and cancer cell stemness. This review summarizes the role of non-coding RNAs in the development of chemotherapeutic resistance in ovarian cancer, including their mechanisms, targets, and potential signaling pathways. This will facilitate the development of novel chemotherapeutic agents that can target these non-coding RNAs and improve ovarian cancer treatment.